Shared and distinct contributions of rostrolateral prefrontal cortex to analogical reasoning and episodic memory retrieval. Issue 3 (10th December 2015) - Westphal, Andrew J.; Reggente, Nicco; Ito, Kaori L.; Rissman, Jesse
Abstract: Rostrolateral prefrontal cortex (RLPFC) is widely appreciated to support higher cognitive functions, including analogical reasoning and episodic memory retrieval. However, these tasks have typically been studied in isolation, and thus it is unclear whether they involve common or distinct RLPFC mechanisms. Here, we introduce a novel functional magnetic resonance imaging (fMRI) task paradigm to compare brain activity during reasoning and memory tasks while holding bottom‐up perceptual stimulation and response demands constant. Univariate analyses on fMRI data from twenty participants identified a large swath of left lateral prefrontal cortex, including RLPFC, that showed common engagement on reasoning trials with valid analogies and memory trials with accurately retrieved source details. Despite broadly overlapping recruitment, multi‐voxel activity patterns within left RLPFC reliably differentiated these two trial types, highlighting the presence of at least partially distinct information processing modes. Functional connectivity analyses demonstrated that while left RLPFC showed consistent coupling with the fronto‐parietal control network across tasks, its coupling with other cortical areas varied in a task‐dependent manner. During the memory task, this region strengthened its connectivity with the default mode and memory retrieval networks, whereas during the reasoning task it coupled more strongly with a nearby left prefrontal region (BA 45) associated with semantic processing, as well as with a superior parietal region associated with visuospatial processing. Taken together, these data suggest a domain‐general role for left RLPFC in monitoring and/or integrating task‐relevant knowledge representations and showcase how its function cannot solely be attributed to episodic memory or analogical reasoning computations. Hum Brain Mapp 37:896–912, 2016 . © 2015 Wiley Periodicals, Inc .